The Effect of Multilingual Environment on Native language Acquisition - Moulai Hacene, Fatima Zohra (My University, 2017)
The present study aims at highlighting the effects of multilingual users on the child’s language acquisition and use, how using multiple languages with children can affect their ability and motivation to learn their mother language. Young children have a great capacity to acquire languages. The main problematic in multilingual living is how to control the quantity of the input due to many reasons including the parental discourse strategy and attitude, experiencing the language in another context and language status. The method followed in this study is participant observation, the analyses of children’s performance taking into consideration the linguistic setting and its impact on the learning process. The results discover that young children’s learning is an easier and faster process even within a multilingual environment but it is all depending on fixing the outside world to guarantee the condition where learning take place.
Keywords: Multilingual environment; Language acquisition; Input